Colonial and Post-colonial Rangeland Enclosures amid Climate Uncertainty: The Case of Maasai Pastoralists of Kajiado County, Kenya - Mugambi, Munene Mutuma (School of African and GenderStuds, Anth and Ling, 2023)
The enclosure of common resources in Kenya's rangelands became more pronounced after Kenya's independence because of adverse land reform policies, which proved ineffective in addressing the prior injustices of the forceful dispossession of Maasai pastoralists by the British colonial authority. The ongoing enclosure of common resources by both state and private capital for economic gain has left the herder community exposed to the adverse effects of climate change. The purpose of this thesis is to examine the adaptive capacity of Maasai to the intersecting stresses of climate change and resource enclosure. It examines the implications of common-resource enclosures for the Maasai livestock economy and the coping mechanisms they have undertaken to build adaptive capacity to changing climate conditions. The analysis employs an ethnographic approach using interviews and participant observation to collect data from field research in Ildamat-Oloyiankalani, Kajiado County, Kenya. The study is embedded in the daily herding and resource foraging practices of Maasai that took place during the prolonged drought period of 2017 and 2018 and in their ongoing experience of the intersecting stresses of climate change and common-resource enclosures. The study unveiled three major insights. First, that a tightening grip over common resources by private property growth has undermined the consensus-based democratic governance of resources, disrupted herders' access rights and exposed them to climate risks. Second, that pastoralists developed collective grazing arrangements and acquired exclusive grazing rights as mechanisms to improve herd mobility and resource access to cope with the intersecting stresses of climate change and the enclosure of grazing commons. Lastly, the study found that the implications of growing resource pressure and climate risk have driven pastoralists to actively assemble to disrupt further enclosure of their commons and to protect their rights. These insights confirm the importance of pastoralists' access rights to rangeland resources. In conclusion, the thesis broadly argues that facilitating extractive capitalism by disrupting pastoralists' access rights through common-resource enclosures adversely affects their ability to cope with the intersecting stresses of climate and environmental change. Therefore, it is critical that resource governing policies facilitate the democratisation of grazing and water resources to protect the commons from further enclosure and to ensure equitable access. This would restore the commons approach and protect the remaining herders' access rights, lowering their vulnerability to the intersecting stresses of climate and environmental change.